Fosfomycin Resistant Enterobacterales IsolatedFrom Chicken Meat in Turkey - Al, S; Dişli, HB; Kurekci, C (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was conducted to obtain the relative prevalence of fosfomycin resistant (FOSr) Enterobacterales in raw chicken meat samples in Turkey. Samples (n=85) were enriched in non-selective media and transferred to MacConkey agar plates containing FOS and glucose-6-phosphate. As a result, FOSr Enterobacterales isolates were detected by a selective method in 27% of raw chicken meat samples (n=23) and identified as Escherichia coli (21/26), Klebsiella oxytoca (2/26), Escherichia vulneris (1/26), Raoultella terrigena (1/26) and Kluyvera intermedia (1/26). PFGE analysis showed 16 different band patterns in Escherichia spp. isolates (n=22) based on the 85% similarity. The minimum inhibitory concentration for FOS against all isolates was determined to be ≥64 mg/L. In addition, the highest rate of resistance was determined for nalidixic acid (72.7%), ampicillin (68.2%), tetracycline (59.1%), trimethoprim-sulfamethoxazole (54.5%), and chloramphenicol (59.1%) among all Escherichia isolates. PCR screening and sequencing identified the presence of fosA4 and fosA3 genes in ten (47.6%) and seven (33.3%) E. coli isolates, respectively. The fosA3 gene has also appeared in K. intermedia, and R. terrigena isolates. Only two E. coli isolates were positive for the blaCTX-M-55 gene, whereas the aac(6’)-Ib-cr gene was identified in eight E. coli and one K. intermedia isolates. In addition, 19 different replicon types were determined by PCR-based plasmid replicon typing with IncFII (n=20) being the most common and followed by IncI1α (n=10), IncFIIS (n=8), and IncFIB (n=8). We report, to our knowledge, the first evidence on the presence of FOSr Enterobacterales isolates in raw chicken meat samples in Turkey that might be an important reservoir for FOSr organisms to humans.